Correlates of Having Never Been HIV Tested among Entrants to Substance Abuse Treatment Clinics: Empiric Findings from Real-World New England Settings. - Chadwick, Jeanne J; Andrade, Leonardo F; Altice, Frederick L; Petry, Nancy M (Journal of psychoactive drugs, 2014)
Abstract Routine testing is the cornerstone to identifying HIV, but not all substance abuse treatment patients have been tested. This study is a real-world evaluation of predictors of having never been HIV tested among patients initiating substance abuse treatment. Participants (N = 614) from six New England clinics were asked whether they had ever been HIV tested. Eighty-five patients (13.8%) reported having never been tested and were compared to those who had undergone testing. Clinic, male gender (adjusted odds ratio (AOR) = 1.91, 95% confidence interval (CI) = 1.07-3.41), and having fewer employment (AOR = 0.31; 95% CI = 0.11-0.88) and medical problems (AOR = 0.40, 95% CI = 0.17-0.99) were independently correlated with having never been HIV tested. Thus, there is still considerable room for improved testing strategies as a clinically significant minority of substance abuse patients have never undergone HIV testing when they initiate treatment.